An Ordinance Concerning Slaves, and Free Negroes and Mulattos, § 1, in Arkansas Gazette, Jan. 12, 1836, at 1 - (:unkn) unknown (My University, 1836)
That no slave or free negro or mulatto whatsoever shall keep or carry, within the limits of said City, any gun, pistol or other fire arm of any kind whatsoever, or any knife, dirk, club or any weapon of offence or defence whatsoever, or any powder, balls or shot; and that any and every such weapon, and any and all such ammunition found in the possession or custody of any negro or mulatto, may be seized by any person,
Keywords: ENSLAVED PERSONS & OTHER MINORITIES